2022
DOI: 10.7759/cureus.32712
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Anxiety and Depression to the Development of Gastroesophageal Disease in the Younger Population?

Abstract: Gastroesophageal reflux disease (GERD) is a condition characterized by the reflux of stomach contents into the esophagus which leads to heartburn and regurgitation. GERD has been categorized its types according to severity. The categories that have been discussed in this study are reflux esophagitis (RE), non-erosive reflux disease (NERD), and Barrett's esophagus. Our study compared various studies and showed that the subjects with GERD had a high level of anxiety and depression. Gastroesophageal reflux diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The following mechanism explains the relationship between psychological factors such as anxiety and clinical manifestations caused by GERD. Certain psychological conditions such as anxiety can cause an increase in gastric acid reflux by reducing pressure on the lower esophageal sphincter, changing esophageal motility, or increasing gastric acid secretion [29].…”
Section: Resultsmentioning
confidence: 99%
“…The following mechanism explains the relationship between psychological factors such as anxiety and clinical manifestations caused by GERD. Certain psychological conditions such as anxiety can cause an increase in gastric acid reflux by reducing pressure on the lower esophageal sphincter, changing esophageal motility, or increasing gastric acid secretion [29].…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, epidemiological studies have revealed several potential risk factors for GERD, including obesity [ 16 ], smoking [ 16 ], alcohol [ 17 ], diabetes [ 18 ], depression [ 4 ] and so on. However, much of the evidence lacked reliability, displaying inconclusive outcomes across various investigations, and the precise cause-and-effect relationship of mediators in these connections was not adequately established.…”
Section: Introductionmentioning
confidence: 99%
“…However, research indicated that approximately 40% of patients, despite undergoing standard acid suppression treatment, did not achieve efficient symptom control. Additionally, prolonged PPI medication presented an elevated risk of adverse reactions, including fractures, gastrointestinal infections, and acute interstitial nephritis [4][5][6]. As a high-prevalent chronic condition, GERD presents substantial economic and health burdens to patients and society [7].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recurrent symptoms seriously affect the patient's quality of life, leading to sleep disorders, decreased body mass index, and an increased risk of esophageal precancerous lesions to 75% [5][6][7] . Notably, research indicates a higher incidence of depression among GERD patients compared to the healthy population, among which approximately 69% of refractory re ux symptoms associated with depression in rGERD [8,9] . This poses a challenge to PPIs in fully alleviating symptoms in affected individuals.…”
Section: Introductionmentioning
confidence: 99%